2003
DOI: 10.1046/j.1540-8167.2003.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dispersion of Refractoriness in Patients with Atrial Fibrillation in the Early Postoperative Period after Coronary Artery Bypass Grafting

Abstract: AERP dispersion is a suitable electrophysiologic indicator for atrial vulnerability. The presence of increased preoperative AERP dispersion and PA interval may indicate patients at high risk for development of AF in the early postoperative period after coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
2
14
1
Order By: Relevance
“…Those patients with induction of AF showed a larger dispersion of refractoriness due to a marked difference between ERP at the right atrium and those obtained along the CS. These findings are in accordance with other authors, who reported shorter ERP in the high right atrium when compared with distal CS in patients with AF [7,21]. This may be explained by a non-uniform distribution of vagal nerve endings, which seems to cause greater changes in refractory period in the RAA than in left atrium [22].…”
Section: Atrial Refractory Periodssupporting
confidence: 92%
See 1 more Smart Citation
“…Those patients with induction of AF showed a larger dispersion of refractoriness due to a marked difference between ERP at the right atrium and those obtained along the CS. These findings are in accordance with other authors, who reported shorter ERP in the high right atrium when compared with distal CS in patients with AF [7,21]. This may be explained by a non-uniform distribution of vagal nerve endings, which seems to cause greater changes in refractory period in the RAA than in left atrium [22].…”
Section: Atrial Refractory Periodssupporting
confidence: 92%
“…Electrical remodelling of the atrial tissue, which is associated with shortening of the atrial refractory period in a heterogeneous way, is known to be related with atrial vulnerability for the occurrence of spontaneous and inducible AF and to favour the maintenance and perpetuation of the arrhythmia [7]. Patients with inducible AF are at an increased risk of AF recurrence, even after pulmonary vein isolation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance of autonomic function could influence the atrial refractory period [25] and initiate atrial arrhythmias in this way [10][11][12]26]. In an electrophysiologic study an increased dispersion of atrial effective refractory period and intraatrial conduction delay was detected in patients with postoperative AF in comparison to patients with sinus rhythm [28]. Thus we could noninvasively detect a delayed atrial conduction and an imbalance of autonomic function which were risk factors for postoperative AF.…”
Section: Properties Of Atrial Fibrillationmentioning
confidence: 92%
“…One important risk factor for AF is intraatrial conduction delay which was reflected by a longer FPD [13,22,27,28]. An imbalance of autonomic function could influence the atrial refractory period [25] and initiate atrial arrhythmias in this way [10][11][12]26].…”
Section: Properties Of Atrial Fibrillationmentioning
confidence: 99%
“…To date, no data have been available concerning the heterogeneity of action potential waveform and underlying ionic mechanisms between RAA and AS. Such information would be highly relevant to susceptibility to AF and to the treatment of AF [18,19].…”
Section: Introductionmentioning
confidence: 99%